An overview of the jury system in Malaysia / Siti Khadijah Mohd Pisol and Nurul Nasihin Ariffin - Mohd Pisol, Siti Khadijah; Ariffin, Nurul Nasihin (2008)
This research is about an overview of the jury system in Malaysia. Jury system was applied in Malaysia during the British colonial days until 1st March 1995. Jury trial is the traditional mode of determining issues of fact at Common Law. Its development dates back far into the sixteenth century. Basically the roles of the jurors include listening to witnesses, determining documents and determining the credibility and weight of the evidence based upon common sense and experience. Jurors are required to follow the law of the case as the judge instructs, and apply the facts to the law, separating out relevant facts from unimportant material. Jurors, as determiners of the facts must be impartial and objective. The application of the jury system is hotly debated recently. Some critics embrace the concept of jury trial. However due to the increase in courtroom technology, and complex litigation, some argue that the system is no longer able to deal with the complexities of modern litigation. This research seeks to out the problems that a rose behind the application of jury trial. The problems were encountered after evaluating the procedure of jury system. However it cannot be denied that jury trial may have its benefit and advantages. Beside that, criminal justice in Malaysia is also being analysed. In conclusion, the elimination of jury trial had resulted in a positive impact injudicial system in Malaysia obviously.